Intervensi Pada Anak Retardasi Mental Usia 7–8 Tahun Dalam Perkembangan Kognitif - Nancy Riana; Lilis Karyawati (UIN Sultan Maulana Hasanuddin Banten, 2019)
The study aims to find out and describe interventions on children of mental retardation age 7-8 years in cognitive development. This research was conducted in SLB Negeri 5 West Jakarta in 2019. The research methods to be used in this study are qualitative methods, with a case study approach, using data triangulation techniques. Data collection techniques are based on observations, interviews and documentation. The research subject is the teacher of grade 1Cb and 1C1d and students. Based on the results of data Pegumpulan obtained that the intervention carried out in children of mental retardation in SLB Negeri 5 West Jakarta in students aged 7 -8 years in cognitive development ie; (1) Learn problem solving, which includes activities to understand classmates ' faces, understand their own objects and others, concentrating on the tasks given, following daily habits; (2) Logical thinking, which includes the activity of sticking mosaics, following the instruction of the teacher, knowing the parts of the body, understanding the concept of size, and counting activities; (3) Thinking symbolically, which includes activities mentioning numbers one to five, mimicking the way of holding stationery, and naming the work made. The results of this study have implications that children who experience mental retardation need special intervention in their development. It must be done early so that the development is optimal. Keywords: children with special needs, early Childhood, Intervention, cognitionReferencesAbdillah, Abu. (2018). Bunyi UUD 1945 Pasal 31 Ayat 1,2,3,4,5 dan Penjelasannya. https://petikanhidup.com/bunyi-uud-1945-pasal-31-ayat-1-2-3-4-5-dan-penjelasannya.htmlBudiman, Asep. (2016). Pemahaman Rendah, Anak Berkebutuhan Khusus Masih Dianggap Negatif. Bandung: Pikiran Rakyat. https://www.pikiran-rakyat.com/bandung-raya/2016/08/21/pemahaman-rendah-anak-berkebutuhan-khusus-masih-dianggap-negatif-377958Delphie, Bandi. (2006). Pembelajaran Anak Berkebutuhan Khusus. Bandung: Refika Aditama. Desmita. Psikologi Perkembangan Peserta Didik. Bandung: Remaja Rosdakarya. (2009)Hildayani, Rini dkk. Penanganan Anak Berkelainan. Tanggerang Selatan: Universitas Terbuka. (2013)Imroatun, I. (2017). Anak Dengan Kebutuhan Fisik Khusus. As-Sibyan : Jurnal Pendidikan Anak Usia Dini, 2(02), 175–185.Jamaris, Martini. (2010). Orientasi Baru dalam Psikologi Pendidikan. Jakarta: Yayasan Penamas Murni. Juniarti, Fitri. (2014). Pengertian Retardasi Mental. https://www.e-jurnal.com/2014/01/pengertian-retardasi-mental.htmlKhodijah, Nyayu. (2016). Psikologi Pendidikan. Jakarta: Raja Grafindo Persada. Kumar, Indra bhushan, Amool R. Singh, dan S. Akhtar. (2009) Social Development of Children With Mental Retardation (India: Ind Psychiatry J. Jan-Jun; 18(1): 56–59. doi: 10.4103/0972-6748.57862). https://www.ncbi.nlm.nih.gov/pmc/articles/PMC3016702/Miles, Matthew B & A. Michael Huberman. (1992). Analisis Dta Kualitatif: Alih Bahasa. Jakarta: UI-Press. Moleong, Lexy J. (2013). Metodologi Penelitian Kualitatif. Bandung: Remaja Rosdakarya. Pakar Komunikasi. 5 Jenis Metode Penelitian Kualitatif Pendekatan dan Karakteristiknya. https://pakarkomunikasi.com/jenis-metode-penelitian-kualitatifPatilima, Hamid. (2007). Metode Penelitian Kualitatif. Bandung: Alfabeta. Santrock, John W. (2004). Educational Psychology. New York: McGraw-Hill. Somantri, T. Sutjihati. (2007). Psikologi Anak Luar Biasa. Bandung: Refika Aditama. Sugiyono. (2008). Metode Penelitian Kuantitatif Kualitatif dan R&D. Bandung: Alfabeta. Sukmadinata, Nana Syaodih. (2010). Metode Penelitian Pendidikan. Bandung: Remaja Rosdakarya. Undang-undang Republik Indonesia No. 20 Tahun 2003 Tentang Sistem Pendidikan Nasional. http://kelembagaan.ristekdikti.go.id/wp-content/uploads/2016/08/UU_no_20_th_2003.pdf